Role of green financing and financial inclusion to develop the cleaner environment for macroeconomic stability: inter-temporal analysis of ASEAN economies - Saydaliev, Hayot Berk; Chin, Lee (Springer, 2022)
The research objective is to assess the role of green financing and financial inclusion in developing a cleaner environment for macroeconomic stability in ASEAN economies. The study attempted to estimate the climate mitigation factor associated with a more sanitary environment between 2012 and 2019. Panel data analysis using the augmented Dicky–Fuller test, Phillip–Perron, and fully modified standard most minor square test provides long-term findings in panel data analysis. In addition, the vector error correction technique was also applied to infer study results. The findings indicate that climate change mitigation indicators have a significant impact on the gross domestic product of ASEAN economies. According to the data, a one percent rise in the green finance index results in a 0.321 percent increase in the amount of pollution removed from the environment. According to the research findings, environmental pollution must be decreased, and energy sources must be switched to more creative and ecologically friendly alternatives. Using study findings, several policy recommendations are offered and suggested for stakeholders for implementation. As per our best understanding, effective implementation of study findings and suggestions maximum chances are developing a cleaner environment and boosting macroeconomic stability in the ASEAN context.